Deoxycholate bile acid directed synthesis of branched Au nanostructures for near infrared photothermal ablation. (July 2015) - Kim, Dong-Hyun; Larson, Andrew C.
Abstract: We report an approach for simple, reproducible and high-yield synthesis of branched GNPs directed by deoxycholate bile acid supramolecular aggregates in Au solution. A growth process involving stepwise trapping of the GNP seeds and Au ions in the deoxycholate bile acid solution yields multiple-branched GNPs. Upon NIR laser irradiation strong NIR absorption for branched GNPs induced photothermal-heating to destroy tumor cells. Subsequently, these branched GNPs were biofunctionalized with cRGD cell penetrating-targeting peptides for photothermal cancer treatment applications. Branched GNPs conjugated with cRGD peptides enhanced internalization of the branched GNPs in BxPC3 human pancreatic adenocarcinoma cells and effectively ablated BxPC3 cells when irradiated with a NIR laser (808 nm). Their potential use as photothermal transducing agents was demonstrated in in vivo settings using a pancreatic cancer xenograft model. The tumors were effectively ablated with cRGD-branched GNPs injection and laser exposure without any observation of tumor recurrence. This firstly reported method for deoxycholate bile acid directed synthesis of branched GNPs opens new possibilities for the production of strong NIR absorbing nanostructures for selective nano-photothermolysis of cancer cells and the further design of novel materials with customized spectral and structural properties for broader applications.